A MUSEUM FRAME OF ODESA LIFE DURING THE FULL-SCALE INVASION (City: History, Culture, Society, 2026)
The article reflects on how, during Russia’s full-scale invasion, Odesa has been rethinking its relationship with urban heritage and redefining the city’s image—an image long reproduced within an imperial frame. The text emphasizes a double context: the city has been a target of sustained Russian propaganda for decades, yet in 2014 it stopped the so-called “Russian Spring,” which makes questions of self-identification especially acute. Writing from the position of a participant in cultural processes, the author stresses that under conditions of extreme испытання the question “who are we?” becomes a resource for survival, while museums function as infrastructure for producing and articulating meaning.After the evacuation of collections in 2022, Odesa’s museums faced a choice: suspend operations or continue without permanent displays. The article outlines institutional responses—from interventions in public space (MSMO’s project Shoulder to Shoulder) to turning emptied galleries into platforms for processing the experience of war (the Languages of War series at the Odesa National Fine Arts Museum, tribute exhibitions to artists killed in the war, and Alevtina Kakhidze’s solo project Dad, I’m in Odesa!). The author also describes local narrative formats for speaking about safeguarding heritage (the Bleschunov Museum’s graphic novel), the Archaeological Museum’s symbolic turn to Snake Island, the opening of the private genocide museum Territory of Memory, and cultural diplomacy through exhibitions in Kraków and Berlin that shape alternative frames for perceiving Odesa as a Ukrainian and European city.A second focus is decolonization: the Odesa National Fine Arts Museum’s work with the Soviet legacy embedded in its collection; public tensions surrounding the transfer of dismantled monuments to Catherine II and Suvorov; and the UNESCO nomination dossier, which proposes an anti-imperial reading of Odesa’s urban phenomenon (port-city development, multiculturalism, entrepreneurship, and democratic practices of coexistence). The article considers the business community initiative Odesa Decolonization, which seeks to shift the city’s myth from a “criminal” trope to an “entrepreneurial” one. The conclusion argues that in wartime museums can remain community centers even without their collections on display—sustaining memory, resilience, and the construction of a future-oriented civic narrative.
Keywords: urban myth, museum, south of Ukraine, Odesa